Evaluation of Resources Development and Installation Tech-niques to Reduce Posttraumatic Stress Disorder Symptoms in Women Victims of Domestic Violence: A Single Case Study - Yudi Kurniawan; Agung Santoso Pribadi; Vriska Putri Rakhmasari (International Journal of Health and Medicine, 2025)
This study aims to evaluate the Resource Development and Installation (RDI) technique to reduce symptoms of Posttraumatic Stress Disorder (PTSD) in female victims of domestic violence. Domestic violence (which falls under the category of intimate partner violence/IPV) is a global public health problem that contributes significantly to women's mental health disorders, including post-traumatic stress disorder (PTSD). Recent systematic evidence shows a strong association between various forms of IPV and adverse mental health outcomes in women, with large variations in prevalence across contexts. Resource Development and Installation (RDI) is a psychological stabilization procedure within EMDR aimed at generating positive resources in individuals exposed to traumatic experiences. The research method used in this study was multiple baseline with a single case (single case research), namely research conducted on subjects with the aim of determining the magnitude of the effect of treatment given repeatedly over a certain period. This study involved three adult female participants who experienced trauma symptoms due to violence perpetrated by an intimate partner in a domestic context. The data analysis technique used in this study was visual inspection by comparing changes in trauma scores in respondents between the baseline and intervention phases. Trauma symptoms were measured using the Harvard Trauma Questionnaire (HTQ). There was a decrease in HTQ scores from an average of 2.9 (presence of PTSD symptoms) before the intervention to 2.1 (minimal). Resources Development and Installation were effective in reducing trauma symptoms in female victims of violence. This was evident in the decrease in trauma symptom scores between before and after the provision of Resources Development and Installation to female victims of violence.